Infrastructure projects in Egypt: A decision-support framework for the selection from World Bank lending instruments - Moussa, Mohamed Bahgat (AUC Knowledge Fountain, 2018)
The funding of large-scale high-risk infrastructure projects is of growing importance in Egypt. The Government of Egypt (GoE) partners with several International Financial Institutions (IFIs) to secure the funding of infrastructure projects that are essential to supporting sustainable development. The World Bank is one of the largest IFIs that support infrastructure projects in Egypt. The World Bank Group is formed of the International Finance Corporation (IFC), International Centre for Settlement of Investment Disputes (ICSID), Multilateral Investment Guarantee Agency (MIGA), the International Bank for Reconstruction and Development (IBRD), and the International Development Association (IDA). The IBRD and the IDA form “The World Bank”. The Bank provides three main financing instruments, namely Development Policy Finance (DPF), Investment Project Finance (IPF), and the relatively recently proposed Program-for-Results (P-for-R). The latter two are currently used to support an array of infrastructure projects dispersed in a variety of developing nations. The aim of this research is to compare between IPF and P-for-R funding mechanisms and to propose a framework for the selection of the best-suited instrument for any given infrastructure project in Egypt. Structured interviews are conducted with 21 international experts working on World Bank financed projects in Egypt in order to identify the criteria for the optimum selection of finance methods, risks associated with different infrastructure projects, and which instrument better addresses each of these risks. It was found that IPF better addresses risks related to Technical Design and Implementation, while P-for-R is better suited for Institutional Capacity and Sector Strategy risks. The outcome of the interviews and the existing literature are analyzed to develop a 4-step framework for the selection of the optimum finance instrument. The developed framework includes a logistic regression model that matches the risk profile of a given project with the most appropriate instrument. Finally, the framework is applied on two case studies in Egypt in order to assess its validity. The first case study, the SRSSP is a sanitation program funded through P-for-R which was confirmed by the devised framework to be the better–suited tool for the nature of the project. The performance of SRSSP was compared to the performance of 2 very similar projects that were funded through IPF and it was verified that the performance of the P-for-R funded SRSSP is more satisfactory. The framework as then applied on another case study which is the GNPP. The GNPP is an IPF project which also matches the output of the framework and its performance has been assessed as satisfactory by the World Bank. It was concluded that the output of developed framework is valid and it can effectively support the selection of the best-suited funding instrument for a given infrastructure project in Egypt.